2013
DOI: 10.1016/j.canlet.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E promotes cancer cell survival, but inhibits migration and invasion

Abstract: Carboxypeptidase E (CPE), a prohormone processing enzyme is highly expressed and secreted from (neuro)endocrine tumors and gliomas, and has been implicated in cancer progression by promoting tumor growth. Our study demonstrates that secreted or exogenously applied CPE promotes survival of pheochromocytoma (PC12) and hepatocellular carcinoma (MHCC97H) cells under nutrient starvation and hypoxic conditions, but had no effect on their proliferation. CPE also reduced migration and invasion of fibrosarcoma (HT1080)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
(62 reference statements)
5
42
0
Order By: Relevance
“…In addition, we found that Talin1 inhibition significantly reduced proliferation of HCC cells, consistent with another study in which Talin1‐knockdown MHCC‐97L cells were significantly more blocked in G 0 /G 1 phase . Some genes also have analogous characteristics, possessing diverse and complex biological functions in regulating tumor progression through distinct pathways . For example, SPARC suppresses glioblastoma cell growth by interfering with growth factor–growth factor receptor interactions, while promoting cell migration and invasion by activating integrin‐regulated kinases including integrin‐linked kinase and FAK, and signaling .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found that Talin1 inhibition significantly reduced proliferation of HCC cells, consistent with another study in which Talin1‐knockdown MHCC‐97L cells were significantly more blocked in G 0 /G 1 phase . Some genes also have analogous characteristics, possessing diverse and complex biological functions in regulating tumor progression through distinct pathways . For example, SPARC suppresses glioblastoma cell growth by interfering with growth factor–growth factor receptor interactions, while promoting cell migration and invasion by activating integrin‐regulated kinases including integrin‐linked kinase and FAK, and signaling .…”
Section: Discussionsupporting
confidence: 89%
“…17,8 CPE has also been implicated in cancer progression [18][19][20][21] and as a neuro-trophic factor regulating brain functions. [22][23][24][25][26] Lately, it was found that CPE is also involved in other biological processes such as bone homeostasis 27 and bowel disease.…”
Section: Discussionmentioning
confidence: 98%
“…6 In both cases, CPE functions as an antiproliferation regulator by interfering with the Wnt pathway. However, it has been shown that under hypoxic conditions CPE can promote cancer cell survival 20 implying that it has pro-survival activities as well. Thus, CPE may have a dual effect on the regulation of the Wnt pathway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the pattern of the CPE-induced activation of the ERK and Akt signaling pathways is similar to classic trophic factors such as BDNF and NGF, an alternative name was given to CPE, “Neurotrophic Factor-α1” (NF-α1), indicating its functions as a trophic factor. In addition to primary cultured neurons, a recent study further found that secreted NF-α1 protects PC12 cells, a pheochromocytoma cell line, against starvation- and hypoxia-induced cell death [22] .…”
Section: Cpe Acts As a Trophic Factor To Promote Neuronal Survivalmentioning
confidence: 99%